Rendimento da incubação e perda de calor dos ovos durante a transferência da incubadora para o nascedouro - Silva, Gabriela Fagundes da [UNESP] (2016)
The incubatory of eggs has great importance in the production chain, since it is the supplier of the production chain. Thus, inefficiency in the incubatory affects the entire production chain. An experiment was performed in order to observe the effects of the broiler breeders and the heat loss of the eggs during the transfer from the hatchery to the hatcher on the yield of the incubation. Eggs from three ages: 26, 32 and 53 weeks of Cobb broiler breeders were incubated. These eggs were separated into two treatments: T0 as the control treatment, which complied with the procedures normally adopted by the incubator company and T1 which used a cooler to transport the eggs during the transfer. For both treatments the transfer took about 10 minutes in all the three repetitions. After the birth it was made the counting of the hatched chicks, of the unhatched eggs, the calculations of hatching and hatchability, the breaking of the unhatched eggs; all to determine at what time of the development the embryonary mortality took place, and the weight of the hatched chicks. The results obtained showed that the eggs of the 26-week breeders had higher infertility, which led to the lower hatching. Hatchability and mortality did not differ between the ages. The weight of the chicks differed in the three ages showing that the chicks of older breeders were heavier. Regarding the heat loss, the results showed that all the places evaluated had temperature and RH out of the recommended in the literature, characterizing the whole route as critical for the temperature control, and that the eggs of T1 suffered less heat loss in the transfers than the T0 eggs. However, the treatment using the cooler did not improve the hatchability indicators and chick weight for the studied transfer time.